2013
DOI: 10.1021/es305026x
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Streams to Legacy Nitrate Sources

Abstract: The influence of hydrogeologic setting on the susceptibility of streams to legacy nitrate was examined at seven study sites having a wide range of base flow index (BFI) values. BFI is the ratio of base flow to total streamflow volume. The portion of annual stream nitrate loads from base flow was strongly correlated with BFI. Furthermore, dissolved oxygen concentrations in streambed pore water were significantly higher in high BFI watersheds than in low BFI watersheds suggesting that geochemical conditions favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
152
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(160 citation statements)
references
References 35 publications
8
152
0
Order By: Relevance
“…At the intermediate and lowest BFI sites-the Potomac River and Difficult Run-groundwaterdischarged nitrate accounted for 69% (1.1 3 10 7 kg) and 58% (3.7 3 10 4 kg) of the total annual load discharged to the stream, respectively. The positive relationship between BFI and the fraction of total loads estimated to be groundwater-discharged loads is consistent with studies that have identified positive relationships between BFI and in-stream loads during base flow conditions [Tesoriero et al, 2009[Tesoriero et al, , 2013Spahr et al, 2010].…”
Section: Groundwater-discharged Nitrate Loadssupporting
confidence: 88%
See 3 more Smart Citations
“…At the intermediate and lowest BFI sites-the Potomac River and Difficult Run-groundwaterdischarged nitrate accounted for 69% (1.1 3 10 7 kg) and 58% (3.7 3 10 4 kg) of the total annual load discharged to the stream, respectively. The positive relationship between BFI and the fraction of total loads estimated to be groundwater-discharged loads is consistent with studies that have identified positive relationships between BFI and in-stream loads during base flow conditions [Tesoriero et al, 2009[Tesoriero et al, , 2013Spahr et al, 2010].…”
Section: Groundwater-discharged Nitrate Loadssupporting
confidence: 88%
“…Therefore, end-member concentrations for groundwater discharge and runoff were determined using the winter BFI-nitrate relationships. Groundwater-discharged end-member concentrations (1.8 6 0.1-2.9 6 0.1 mg/L as N), which represent the nitrate concentration in the slowly varying subsurface flow paths contributing to the stream, were greater than runoff end-member concentrations (0.8 6 0.1-1.6 6 0.1 mg/L as N; [Sanford and Pope, 2013;Tesoriero et al, 2013]. Indeed, the age of groundwater in the Potomac River watershed has been estimated to range from 10 to 20 years [Michel, 1992;Phillips et al, 1999].…”
Section: Groundwater-discharged Nitrate Loadsmentioning
confidence: 98%
See 2 more Smart Citations
“…2014). Nitrogen leaching from legacy sources has been recognized as a primary reason for these limited results, due to the long lag time (ranging from years to decades) elapsed between watershed N inputs and riverine export (Sebilo et al 2013;Sanford and Pope 2013;Tesoriero et al 2013). Exceedance of water quality targets has prompted regulatory agencies to reevaluate nutrient management standards, measures, and guidelines (Sharpley et al 2013).…”
Section: Introductionmentioning
confidence: 99%